Assessing the Possibility of Appearing RIP Current at Quy Nhon Beach, Binh Dinh Province - Xuan Loc, Nguyex; Dinh Duc, Dang (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 4, 2019)
RIP current is a strong, popular water flow at beaches in Vietnam as well as in the world, with the direction of flow from the shore to the sea. This is a dangerous flow, each year there are unfortunate accidents for swimmers. This study used the measured data source implemented by the Center for Environmental Fluid Dynamics in 2018 to build the model MIKE 21 Coupled for simulating the hydrodynamic field and the rip current at Quy Nhon beach area. Through calculation scenarios under different conditions show that, the area near the amusement park (An Duong Vuong road) and the southern-most area of Quy Nhon beach are likely to appear rip current in the northeast wind season. In the southwest monsoon season, the intensity of the rip current is strong, appearing near the Victory Monument area. These areas are often crowded by swimmers with local people and tourists, so pay attention to avoid accidents that may happen.